Equal Channel Angular Extrusion Simulation of High-Nb Containing β-γ TiAl Alloys - Lai-qi Zhang; Xiang-ling Ma; Geng-wu Ge; Yong-ming Hou; Jun-zi Zheng; Jun-pin Lin (Advances in Materials Science and Engineering)
TiAl alloys containing high Nb are significantly promising for high-temperature structural applications in aerospace and automotive industries. Unfortunately the low plasticity at room temperature limits their extensive applications. To improve the plasticity, not only optimizing the opposition, but also refining grain size through equal channel angular extrusion (ECAE) is necessary. The equal channel angular extrusion simulation of Ti-44Al-8Nb-(Cr,Mn,B,Y)(at%) alloy was investigated by using the Deform-3D software. The influences of friction coefficient, extrusion velocity, and different channel angles on effective strain, damage factor, and the load on the die were analyzed. The results indicate that, with the increasing of friction coefficient, effective strain is enhanced. The extrusion velocity has little effect on the uniformity of effective strain; in contrast it has large influence on the damage factor. Thus smaller extrusion rate is more appropriate. Under the condition of different channel angles, the larger one results in the lower effective strain magnitude and better strain distribution uniformity.